2012
DOI: 10.1097/bsd.0b013e31825d63c4
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Paravertebral Muscle Activity in Lumbar Kyphosis Patients by Surface Electromyography Compared With Lumbar Spinal Canal Stenosis Patients and Healthy Volunteers

Abstract: Our study revealed the constant activity of paravertebral muscles and the susceptibility to muscle fatigue in patients with LDK. The quantification of muscle activity by surface EMG may show the pathology of LDK, and the decrease in muscle activity in the standing position may be a potentially useful index for guiding treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Paraspinal muscle activity is increased in lumbar kyphosis patients compared with age-matched LSS patients. 33 Chronic increased paraspinal muscle activity in our study subjects may have accelerated PGC-1α mRNA expression in the paraspinal muscles. In fact, Pilegaard et al 34 demonstrated that PGC-1α transcription and mRNA content in vastus lateralis muscles increase after exercise, especially in the trained leg compared with the untrained leg.…”
Section: Discussionmentioning
confidence: 69%
“…Paraspinal muscle activity is increased in lumbar kyphosis patients compared with age-matched LSS patients. 33 Chronic increased paraspinal muscle activity in our study subjects may have accelerated PGC-1α mRNA expression in the paraspinal muscles. In fact, Pilegaard et al 34 demonstrated that PGC-1α transcription and mRNA content in vastus lateralis muscles increase after exercise, especially in the trained leg compared with the untrained leg.…”
Section: Discussionmentioning
confidence: 69%
“…A report found fatty degeneration of multifidus muscle on the concave side of degenerative scoliosis [12], while hyperplasia of the multifidus muscle and iliopsoas muscle has been reported regarding the convex side of degenerative scoliosis [13]. On the other hand, when Enomoto et al [14] took surface electromyograms of paravertebral muscle activity, they found that compared to lumbar spinal canal stenosis (LSCS), patients with degenerative lumbar scoliosis (DLS) had high paravertebral muscle activity. Yagi et al [11] measured appendicular skeletal muscle mass in patients with DLS and LSCS by DXA and reported that there was no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some patients complain of recurrent chronic LBP and sagittal decompensation related to posture even after surgical correction of kyphotic spinal deformities 2 , 31 ) . Exercises that help train lumbar stabilizing muscles are typically adopted for conservative treatments of chronic LBP and the correction of kyphotic postures 16 , 17 , 18 , 19 , 20 , 32 ) . Patients with LBP cannot sufficiently activate the deep lumbar stabilizers 13 , 14 , 15 ) , and thus, extensive LM muscle atrophy is a characteristic of LDK patients 33 ) .…”
Section: Discussionmentioning
confidence: 99%